Reinventing the Renaissance
XII, 325 p.
Keywords: The plays of Shakespeare and his contemporaries has inspired interpretations in every genre and medium. This book offers perspectives on the ways in which practitioners have used Renaissance drama to address contemporary concerns and reach new audiences. It provides a resource for those interested in the creative reception of Renaissance drama.